Cascaded collision lattice Boltzmann model (CLBM) for simulating fluid and heat transport in porous media. (2nd September 2017) - Shah, Nimit; Dhar, Purbarun; Chinige, Sampath Kumar; Geier, Martin; Pattamatta, Arvind
ABSTRACT: The present paper reports a cascaded collision lattice Boltzmann model for the simulation of an incompressible two-dimensional fluid flow in a porous media regime. The cascaded model is first validated for the nonporous regime using limiting conditions against previous finite element model reports. Subsequently, the cascaded collision model is applied to the lid-driven porous-filled cavity to demonstrate the largely augmented numerical stability of the model against the more common Bhatnagar–Gross–Krook and multiple relaxation time collision models. Finally, the cascaded model is applied to an inflow–outflow case of flow and heat transfer over a porous bluff body to showcase its efficiency in capturing the complex fluid and heat transport phenomenon through porous media.